2015
DOI: 10.1039/c5cc04551g
|View full text |Cite
|
Sign up to set email alerts
|

Efficient photocatalytic water oxidation catalyzed by polyoxometalate [Fe11(H2O)14(OH)2(W3O10)2(α-SbW9O33)6]27− based on abundant metals

Abstract: An eleven iron-containing nanoscale inorganic polyanionic oxide cluster was reported as the first example for exceptional photocatalytic water oxidation. Under optimal conditions, a remarkable turn-over number (TON) of 1815 ± 50 and a turn-over frequency (TOF(initial)) of 6.3 s(-1) over were achieved for water oxidation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 94 publications
(32 citation statements)
references
References 32 publications
(9 reference statements)
0
28
0
1
Order By: Relevance
“…We designed and obtained a novel Fe‐based POM [Fe 11 (H 2 O) 14 (OH) 2 (W 3 O 10 ) 2 (α‐SbW 9 O 33 ) 6 ] 27− ( 4 ) as photocatalytic WOC in 2015 . This POM possesses multiple intriguing structural feature.…”
Section: Visible Light‐driven Water Oxidation Reaction Catalyzed By Wmentioning
confidence: 99%
“…We designed and obtained a novel Fe‐based POM [Fe 11 (H 2 O) 14 (OH) 2 (W 3 O 10 ) 2 (α‐SbW 9 O 33 ) 6 ] 27− ( 4 ) as photocatalytic WOC in 2015 . This POM possesses multiple intriguing structural feature.…”
Section: Visible Light‐driven Water Oxidation Reaction Catalyzed By Wmentioning
confidence: 99%
“…The initial reaction rate of 7.9 mmol min −1 (the oxygen evolution rate in the first 60 s of light illumination) and TOF initial (TON 1 min/60 s) of 6.3 s −1 in the photocatalytic oxidation with the Fe‐POM are the largest among the data in Table . The quantum yield [(initial O 2 formation rate)/(photon flux)] of 47 % is also the highest value ever reported for the homogeneous photocatalytic water oxidation because the quantum yield of 50 % corresponds to 100 % quantum efficiency (two photons are required to produce four equivalents of [Ru(bpy) 3 ] 3+ , which oxidize water to O 2 with WOC) . Isotope‐labeling water oxidation experiments using 18 O‐enriched water instead of H 2 16 O demonstrated that the evolved oxygen comes from water‐derived oxygen atoms .…”
Section: Homogeneous Catalystsmentioning
confidence: 99%
“…[ www.chemasianj.org quantum yield [(initialO 2 formation rate)/(photonflux)] of 47 % is also the highest value ever reportedf or the homogeneous photocatalytic water oxidation because the quantum yield of 50 %c orresponds to 100 %q uantum efficiency (two photons are required to produce four equivalents of [Ru(bpy) 3 ] 3 + ,w hich oxidize water to O 2 with WOC). [41] Isotope-labeling water oxidation experiments using 18 O-enriched water instead of H 2 16 O demonstrated that the evolved oxygen comesf rom water-derived oxygen atoms. [41] In catalytic water oxidation, homogene-ous metal complexes are often claimed as precatalysts,w hich decompose under oxidizing conditions to insoluble metal oxides that are the real catalysts as discussed in the next section.…”
Section: Homogeneous Catalystsmentioning
confidence: 99%
“…[1][2][3][4][5][6]. The most e ective and facile approach for constructing new CPs is the judicious choice of various organic linkers such as benzenecarboxylates and N-donor ligands.…”
Section: Discussionmentioning
confidence: 99%